2018
DOI: 10.1002/chem.201801670
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Asymmetric Allylic Alkylations of Colby Pro‐Enolates with MBH Carbonates: Enantioselective Access to Quaternary C−F Oxindoles

Abstract: Owing to the innovative applications of fluorinated compounds in many areas of technology and medicine, methods for the preparation of C-F quaternary fluorine containing compounds are in extremely high demand. Here, we report the discovery of a general procedure for an S 2 reaction catalyzed by Pd/Ding-SKP-type ligands, and that occurs between Colby pro-enolates with MBH carbonates to afford the corresponding products featuring two consecutive stereogenic carbons, including a C-F quaternary stereogenic center.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 103 publications
1
17
0
Order By: Relevance
“…Thus, there is a clear necessity to conduct tests to assess the magnitude of the SDE for the processes applied to samples. However, despite a clear call for conducting SDE tests in the past [ 174 ], only a few groups [ 80 , 135 , 167 , 171 , 172 , 173 , 175 , 176 , 177 , 178 , 179 , 180 , 181 ] have taken on the recommendation, but we hope that with the updated and improved recommendations described herein, which cover chromatography and processes involving gas-phase transformations such as evaporation or sublimation, that it will become standard practice for the conduct of high-quality research involving enan-tioselective reactions, natural products, and other work involving chiral compounds.…”
Section: Conclusion and Afterwordmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a clear necessity to conduct tests to assess the magnitude of the SDE for the processes applied to samples. However, despite a clear call for conducting SDE tests in the past [ 174 ], only a few groups [ 80 , 135 , 167 , 171 , 172 , 173 , 175 , 176 , 177 , 178 , 179 , 180 , 181 ] have taken on the recommendation, but we hope that with the updated and improved recommendations described herein, which cover chromatography and processes involving gas-phase transformations such as evaporation or sublimation, that it will become standard practice for the conduct of high-quality research involving enan-tioselective reactions, natural products, and other work involving chiral compounds.…”
Section: Conclusion and Afterwordmentioning
confidence: 99%
“…It should be pointed out that amides 25 represent a combination of two SDE-phoric groups, -CF 3 and -CONH-, leading to strong homo-and heterochiral intermolecular interactions-the foundation of the SDE phenomenon. Considering literature data [87,[123][124][125] and our own experience in the synthesis and properties of fluoro-organic compounds, in particular, catalytic enantioselective reactions [167][168][169][170][171][172][173], we can confidently conclude that practitioners working with -CF 3 -containing compounds should be ready to encounter noticeable magnitudes of the SDEvC (i.e., ∆ee >5%).…”
mentioning
confidence: 91%
“…The organocatalytic allylic monofluoroalkylations of 2 with fluoromethyl(bisphenylsulfones), [19e,f] 2‐fluoromalonates, [19h] or α‐fluoro‐β‐keto esters [19i] have also been explored by the groups of Shibata, Jiang, and Rios. In addition, Han, Soloshonok, Hayashi developed a palladium‐catalysed asymmetric allylic alkylation of 3‐fluorooxindole derived Colby pro‐enolates with MBH carbonates [19j] . Nevertheless, the introduction of an α ‐ gem ‐difluoroketone moiety to access multifunctional α ‐difluoroalkylated acrylate esters via such strategy remains an unaddressed synthetic challenge.…”
Section: Figurementioning
confidence: 99%
“…25,26 Despite the broad application of Morita-Baylis-Hillman (MBH) adducts as functionalized allylic synthons, good regio-and enantiocontrol of metal-catalyzed C1-selective adducts has not yet been realized. [27][28][29][30][31][32] The compherehsive studies on palladium-catalyzed AAA reactions by Trost and co-workers revealed that the regioselectivity can be modulated by both strics and electronics of the ligand. [33][34][35][36] The nucleophilic attack of α-CF 3 enolate from Re/Si faces to either terminal of the π-allyl-metal complexes would result in a number of stereoisomers.…”
Section: Introductionmentioning
confidence: 99%